Changes in clinical indices of multimorbidity and frailty predict subsequent cognitive decline: Findings from the Look AHEAD and Look AHEAD MIND studies. (31st December 2021) - Espeland, Mark A.; Bahnson, Judy; Evans, Joni K.; Hayden, Kathleen M.; Justice, Jamie; Johnson, Karen C.; Johnston, Craig; Munshi, Medha; Simpson, Felicia R.; Kritchevsky, Stephen B.
Abstract: Background: Two common features of aging are increases in the number of chronic diseases and in the number of deficits in functional, behavioral, and clinical characteristics. Accordingly, indices of multimorbidity and deficit accumulation (i.e. frailty indices) have been promoted as clinical markers of biological aging. As such, it is to be expected that changes over time in these indices should be predictive of downstream changes in important functions, such as cognition. Method: We examined associations that 8‐year changes in 1) a multimorbidity index comprised of 9 chronic diseases (e.g. CHD, cancer, depression) and 2) a frailty index (FI) based on deficit accumulation in 38 functional, behavioral, and clinical characteristics had with subsequent standardized measures of cognitive function over 10 years. We drew data from the Look AHEAD clinical trial of a multidomain intensive lifestyle intervention (ILI) in 3841 adults, aged 45‐76 years at baseline, who were at risk for accelerated biological aging due to overweight/obesity and type 2 diabetes mellitus, and who underwent cognitive assessment. The domains of memory, attention, and executive function were assessed with validated instruments and combined to form a composite cognitive measure. Result: 1501 (39%) of the cohort had increases of one and 867 (23%) had increases of > 2 chronic diseases. Older individuals, males, and non‐Hispanic Whites tended to be over‐represented among those with the greatest increase in multimorbidities. The 33%ile of the distribution of FI changes was ‐0.005 and the 67%ile was 0.048. Greater FI increases tended to occur among individuals who were older, non‐Hispanic White, heavier, and who had greater baseline multimorbidity. Changes in multimorbidity and FI were moderately correlated (r=0.25; p<0.001). As seen in the attached table, greater increases in both multimorbidity and FI were associated with subsequently worse levels of executive function, attention, and composite cognitive function (p<0.001). While assignment to ILI was associated with smaller increases in both indices of aging, this did not translate overall to better cognitive functioning. Conclusion: Accelerated aging, as captured by these geroscience‐informed indices, predicts subsequent poorer cognitive function. However, whether interventions generally targeting multimorbidity and FI reduce risks for cognitive impairment remains to be seen.